The Existence of The Malay House ‘Limas Potong’ In the Midst of Modernization Currents in the City of Batam 1970-2022 - Monikasari Monikasari*; Fitriyanti Fitriyanti (Universitas Syiah Kuala, 2023)
The purpose of this study was to determine the impact of the modernization of the city of Batam on the existence of the Malay House Limas Potong. The method used in this research is historical research. The steps in this research are heuristics, source criticism, interpretation, and historiography. The results of the study show that the very first simple industrial concept in Batam, which began in 1898, was the Pertuan Muda of Riau, Raja Muhammad Yusuf-Ahmadi on behalf of the Riau Lingga Kingdom, who granted part of Batam Island land to King Abdullah, Raja Ali Kelana and Raja Muhammad Thahir. In 1978 B.J Habibie changed the course of Batam's development. Batam was transformed into the direction of industrial, service, trade,transhipment and tourism. The Malay House Limas Potong once dominated the architectural forms of houses in Batam City. Currently, the construction of a Malay house with the traditional architecture of the Malay House Limas Potong is no longer a prima donna. Construction efficiency, land availability, difficulty in obtaining raw materials, and up to the development of today's architectural models have changed a lot. The only Malay House Limas Potong currently in Batam City is in Kampung Melayu, Nongsa District.